Spatiotemporal occurrence, distribution, and risk of steroid hormones along the coast of Guangdong, China - Zhao, Xing; Jiang, Yunlin; Deng, Hanqiang; Lu, Yao; Li, Suimin; Jiang, Yuxia; Sun, Kaifeng (Frontiers in Marine Science, 2025)
IntroductionSteroid hormones are widely present in the environment and pose potential risks to organisms. Previous studies of steroid hormones have predominantly focused on terrestrial environments, with few studies conducted in marine environments.MethodsIn this study, we analyzed the occurrence of 44 steroid hormones in seawater, sediment, and marine organisms collected from the coast of Guangdong, China.ResultsTotal concentration of steroid hormones ranged from 0.11 to 30.15 ng/L in seawater, ND to 8.58 ng/g (dw) in sediments, and ND to 80.52 ng/g (ww) in organisms. The highest average concentrations of steroid hormones detected in seawater, sediments, and marine organisms were progestins, estrogens, and glucocorticoids, respectively. Steroid hormone concentrations in seawater were significantly higher during the dry season than the rainy season. The concentrations of steroid hormones in Guanghai Bay, the Pearl River Estuary, Daya Bay, and Zhelin Bay were significantly higher than those in other bays.DiscussionNegative correlations were observed between steroid hormones and salinity, indicating a potential continental input. Risk assessment results indicated that 17α-ethinylestradiol in Zhelin Bay posed high risks. Nevertheless, the consumption of seafood does not pose a significant health risk to humans. To the best of our knowledge, this is the first study to concurrently analyze androgens, glucocorticoids, progestins, and estrogens in water, sediment, and organisms from diverse marine environments.